TANTANGAN TUGAS WAKIL KEPALA DAERAH SUATU TINJAUAN YURIDIS MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - ibrahim (FAKULTAS HUKUM UM PAREPARE, 2020)
The position of Deputy Regional Head is regulated in Law No. 23 of 2014,. However, this Law does not explicitly regulate the duties of Deputy Regional Heads because almost all of their duties are attached to the duties of regional heads by using the term